Pengujian Komitmen Multidimensional Allen dan Meyer dalam Konteks Pemasaran Jasa: Studi Empiris pada Perusahaan Jasa Kategori People Processing - Tjahyadi, Rully Arlan (International Research Journal of Business Studies, 2009)
The purpose of this study is to investigate the extent to which customer satisfaction influence multidimensional commitment, repurchase intention, and advocacy intention. This research also invetigates the impact of multidimensional commitment on repurchase intention and advocacy intention. The model was examined in the context of a service relationship—people processing. This study conducted at Bandung using survey to 200 respondents. Structural equation modelling (SEM) is used to examine the effect of customer satisfaction on multidimensional commitment, repurchase intention, and advocacy intention, and also examine the effect of multidimensional commitment on repurchase intention and advocacy intention. This research found that customer commitment (affective and normative) serves as a partial mediator of the customer satisfaction-future intention relationship. This research also found that normative commitment was strongly and positively related to repurchase intention. Affective commitment was positively related to repurchase intention and advocacy intention. In addition, this research found that customer satisfaction was strongly and positively related to multidimensional commitment. Customer satisfaction was strongly and positively related to repurhase intention and advocacy intention. These findings have important implication that service providers have to focus attention on both the evaluative force (customer satisfaction) and the relational forces (customer commitment) that derive crucial customer behaviors.